UNDERSTANDING THE VALUES OF PANCASILA AS THE FOUNDATION OF THE STATE IN SOCIETY LIFE - Afifuddin Afifuddin; Toriq Najir (Social Sciences and Humanity Studies, 2022)
Understanding the values of Pancasila which is still lacking in society, makes people less obedient and tends to conflict with the laws and regulations that have been set. In writing this journal, the author uses the literature study method, namely by reading and searching from books, journals, laws and other literature study sources that are relevant to the subjects and problems that will be discussed in this journal. This journal writing activity aims to provide further understanding of what Pancasila is, what its functions and positions are as well as what values are contained in its precepts and how to apply it in everyday life.